Missed Pediatric Monteggia Fractures. Issue 6 (June 2018) - Hubbard, James; Chauhan, Aakash; Fitzgerald, Ryan; Abrams, Reid; Mubarak, Scott; Sangimino, Mark
Abstract : Careful scrutiny of radiographs is important in the assessment of pediatric elbow injuries. Disruption of the radiocapitellar line and an increased bow of the posterior ulnar border are sometimes subtle signs of a Monteggia injury. An attempt at closed reduction up to 4 weeks after injury has been cited in the literature as successfully treating some missed injuries. Operative reduction of chronic radial-head dislocation provides good to excellent range of motion and functional outcome in the setting of irreducible chronic radial-head dislocation. Ulnar osteotomy and correction of the ulnar deformity component of the missed Monteggia injury are the key to indirect anatomic reduction of the radiocapitellar joint. Supplemental procedures aimed at increasing the stability of the radiocapitellar joint (e.g., annular ligament reconstruction, radiocapitellar Kirschner wire fixation, radioulnar Kirschner wire fixation) should be directed by a thorough assessment of radiocapitellar stability following ulnar osteotomy and correction of the ulnar deformity.